2020
DOI: 10.31274/jctp.11013
|View full text |Cite
|
Sign up to set email alerts
|

Metro and Non-Metro Variation in Postsecondary Enrollment: The Role of Race, Ethnicity, and Residential Location in Texas

Abstract: This study used a spatial approach to explore metropolitan and nonmetropolitan variation of college enrollment at the interplay of place and race within the state of Texas. Analyzing Integrated Public Use Microdata Series (IPUMS-USA) data and using population proportions as well as regression methods, we pay particular attention to the racial/ethnic diversity in non-metro areas and its relationship with college enrollment. We find geography is a factor in the college enrollment racial/ethnic gaps in nonmetropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 27 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…I deliberately chose these communities to build on past research by Sansone et al (2020), who found a relationship between Texas's rural residency and the proportion of Latinos living in the rural area. More specifically, Sansone et al (2020) found that students in rural areas in Texas where large proportions of Latinos lived were the least likely to enroll in college when compared with their urban and suburban counterparts. Using the purposive method (Creswell, 2013), I selected rural communities from multiple high schools across three rural regions in South Texas.…”
Section: Site Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…I deliberately chose these communities to build on past research by Sansone et al (2020), who found a relationship between Texas's rural residency and the proportion of Latinos living in the rural area. More specifically, Sansone et al (2020) found that students in rural areas in Texas where large proportions of Latinos lived were the least likely to enroll in college when compared with their urban and suburban counterparts. Using the purposive method (Creswell, 2013), I selected rural communities from multiple high schools across three rural regions in South Texas.…”
Section: Site Selectionmentioning
confidence: 99%
“…All these hardships have been amplified by COVID-19 (Noe-Bustamante, et al, 2021) as well as anti-immigration, anti–English language learner, and anti-Latino federal policy regimes (Núñez, 2014). As such, Latino youth living in rural areas where large populations of Latinos reside are less likely to benefit from college opportunities, and they may continue to experience greater social and economic losses that will have disparate impacts on the individuals, but also on the rural regions where they live (Sansone et al, 2020).…”
Section: Introduction To Issue Of Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…Rural Latino communities of color have: For more detail on these findings, read a recent study (Sansone et al, 2020) and report (Leal et al, 2021). Colleges and Universities, to provide financial support to local and regional higher education institutions that serve rural Latino students.…”
Section: Barriers To College-going Opportunities For Latino Youth Liv...mentioning
confidence: 99%
“…For more detail on these findings, read a recent study (Sansone et al, 2020) and report (Leal et al, 2021) .…”
Section: Barriers To College-going Opportunities For Latino Youth Liv...mentioning
confidence: 99%